Guidelines for Mental Health Interventions during Disasters at the "Dr. Gustavo Aldereguía - Teresa Rodríguez Rodríguez; Víctor René Navarro Machado; Deysi Santana Castellón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
These guidelines for mental health intervention within a hospital in cases of catastrophic situations have been prepared not only under the national standards but under the Pan-American Health Organization ones taking into account the specialists and experts' experience on the topic and it has had the approval of the Scientific Council of the University General Hospital "Dr. Gustavo Aldereguía Lima" from Cienfuegos. The guidelines describe the group of procedures to develop in the different cycles of disaster reduction (planning, quip and recovery) mainly those related to patients, family members and hospital staff. This written record gathers the main psychological symptoms and diseases that result from these difficult situations and the main psychological techniques for such situations.